New tourism route planning for the Anyue grottoes in Sichuan, China: Fusion of personalization and data analysis - Yanping Deng; Miaole Hou; Beibei Zhao; Su Yang; Hongchao Fan; Yang Xie (International Journal of Applied Earth Observations and Geoinformation)
With the surge in cultural heritage tourism, personalized tourism route planning has emerged as a crucial strategy to enrich tourists’ experiences. Our objective is to establish a personalized tourism route recommendation and evaluation system. This system will leverage the Analytic Hierarchy Process (AHP) and Delphi method to assess the factors influencing the travel decisions of city-life lovers, cultural-attraction seekers, and selective sightseers. Subsequently, we will gather Points of Interest (POI) data related to these influencing factors and overlay with 147 Anyue grottoes point data, to get the grotto temples in the core area of each type of POIs, and then these grotto temples latitude and longitude coordinates into the Ant Colony Optimization (ACO) to meet the above three categories of the target group of tourists, respectively, the distance of the shortest tour path. Ultimately, this process will lead to the recommendation of personalized Anyue grottoes tour routes, offering tourists customized travel experiences. Based on this approach, we aim to explore and optimize new tourism paths at Anyue grottoes. Our endeavor in personalized tour route recommendation not only enhances tourist satisfaction but also provides data and theoretical support for the tourism industry at Anyue grottoes. It contributes to the construction of the digital display center at Anyue grottoes and offers a viable solution for personalized tourism services at other cultural heritage sites.